The Effect of Jigsaw Cooperative Learning Models with Assisted Augmented Reality (AR) on Mathematics Understanding Concept Ability - Faradillah, Ayu; Sena, Andika Ghabira (Journal of Arts and Education, 2024)
The objective of this study was to know if there is an effect of augmented reality (AR)-supported cooperative learning jigsaw on students' ability to understand concepts. Quantitative design with a single post-test was the method used in this study. The study tool is a descriptive test with 5-item questions and 2-item questions for each indicator. The tool was validated by expert instructors and expert teachers after the tool was validated and then tested on 81 students. Testing this device using a Rasch model, Cronbach's Alpha (kr-20). After the instrument is declared valid and reliable, it is further tested in the experimental class and the control class. Based on data analysis using Cohen's d, The Cohens test showed a significant effect of AR-assisted jigsaw learning on the ability to understand concepts with d = 1.28 meaning very high (ES 1.2). It can be concluded that with AR-supported jigsaw learning, the ability to understand concepts has increased significantly compared to conventional learning.